A Proposed Model to Analyze the Impact of Back-end Logistics Capabilities as a Mediating Variable in Improving the Efficiency of Operational Performance: An Applied Study on a Sample of Industrial Companies Operating in the Egyptian Market - Tawfik, Mabrouk Attia Mabrouk (The Arab Journal of Administration, 2024)
Interest in logistics concepts has increased in the literature of supply and supply chains in the recent period, despite the absence of a scientific study (within the knowledge of the researcher) on the role that back-end logistics plays in improving the operational performance of companies in general and industrial companies in particular. And based on a field study that included 50 industrial companies operating in the Egyptian market, during which the study and evaluation of the impact of the relationship between the independent variables that affect the capabilities of the back-end logistics as an intermediate variable (customer orientation, customer opportunism, commitment to resources, contractual arrangements) and its impact on the dependent variable, performance Operational. The researcher concluded that there is a positive moral correlation between the commitment to resources and contractual arrangements and the background logistical capabilities as an intermediate variable, and the researcher also concluded that there is a negative moral correlation between customer opportunism and the background logistical capabilities as an intermediate variable, and a direct positive moral correlation was found between Back-end logistical capabilities and operational performance improvement in the industrial companies under study and research. It was also found that there was no significant relationship between customer orientation and background logistical capabilities as a mediating variable.